2022
DOI: 10.5194/os-18-143-2022
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven upwelling and surface nutrient delivery in a semi-enclosed coastal sea

Abstract: Abstract. Wind-driven upwelling is an important control on surface nutrients and water properties in stratified lakes and seas. In this study, a high-resolution biophysical coupled model is used to investigate upwelling in the Strait of Georgia on the Canadian Pacific coast. The model is forced with surface winds from a high-resolution atmospheric forecast and has been tuned in previous studies to reproduce extensive observations of water level, temperature, salinity, nutrients and chlorophyll with competitive… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
(114 reference statements)
0
6
0
Order By: Relevance
“…The wind forcing used (HRDPS, see model description) has 2.5 km spatial resolution and hourly temporal resolution, and it is used operationally by Environment Canada in the Canadian Pacific region. The skill of the HRDPS wind product in this region when compared to local meteorological stations has been evaluated by a previous study and accurately reproduces the climatology of observed wind magnitudes and directions (Moore-Maley and Allen, 2022). We first interpolate this product onto the model grid and then extract hourly wind speed.…”
Section: Wind Strengthmentioning
confidence: 82%
See 3 more Smart Citations
“…The wind forcing used (HRDPS, see model description) has 2.5 km spatial resolution and hourly temporal resolution, and it is used operationally by Environment Canada in the Canadian Pacific region. The skill of the HRDPS wind product in this region when compared to local meteorological stations has been evaluated by a previous study and accurately reproduces the climatology of observed wind magnitudes and directions (Moore-Maley and Allen, 2022). We first interpolate this product onto the model grid and then extract hourly wind speed.…”
Section: Wind Strengthmentioning
confidence: 82%
“…In contrast, the CSoG (cluster 3/sky blue) shows the lowest variability between summer and winter energy magnitudes. Summer wind energies are actually higher in the CSoG than in the NSoG, likely due to the long wind fetch length in the CSoG, as summer winds in the Salish Sea are predominantly northerly (Thomson, 1981;Moore-Maley and Allen, 2022). Average vertical eddy diffusivity is lowest in the CSoG (Fig.…”
Section: Central Strait Of Georgiamentioning
confidence: 93%
See 2 more Smart Citations
“…Year-class strength is determined by survival of the vulnerable larval stage, which in turn is strongly dependent on environmental factors affecting successful development 8 . One such environmental factor is ocean acidification (OA), to which the NE Pacific may be particularly vulnerable due to naturally high concentrations of aquatic CO 2 from both natural and anthropogenic drivers including upwelling, low buffering capacity, riverine input and eutrophication 9 14 . Detrimental effects of future projections of ocean acidification levels have been documented in experiments with embryonic and larval Pacific and Atlantic herring ( Clupea harengus ), with lowered condition factor, developmental delays and malformations reported at CO 2 levels as low as 1000 µatm 15 18 , levels which already occur episodically in coastal regions including the Salish Sea 19 22 .…”
Section: Introductionmentioning
confidence: 99%